Board Attributes and Earnings Management of Listed Deposit Money Banks in Nigeria - Bala, Hussaini; Daddau, Haruna; Umar, Musa Sulaiman; Miko, Nuraddeen Usman; Mazadu, Saifullahi Abdullahi (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2023)
This research examined the relationship between board attributes and earnings management of deposit money banks listed on Nigeria Stock Exchange for ten years period (2010-2019). Fourteen deposit money banks listed on Nigerian Stock Exchange as at 31st December, 2019 were selected as the samples using census sampling method. Multiple linear regression technique was employed as technique of data analysis. The results shows that board academic and board credit increased and reduced earnings management respectively and insignificantly while board audit reduced the tendencies of managers to manage earnings significantly. Thus, it is recommended that regulators of Nigerian listed deposit money banks should encourage the constitution of audit committee in Nigerian listed deposit money banks. This is because it has proved to play an important role in checkmating unwanted discretionary accruals and improves the earnings quality in the banks.